Identification and characterization of the structure genes involved in anthocyanin biosynthesis in flowers of Cymbidium species - Zhao, Kunkun; Xie, Junyi; Zheng, Yihong; Yang, Xiaodong; Wang, Yunzhu; Zhang, Xue (Frontiers in Plant Science, 2026)
The Orchidaceae family is renowned for its remarkable floral diversity, showing a wide range of colors primarily influenced by pigments especially anthocyanins. Cymbidium haematodes is a terrestrial orchid characterized by vibrant flower colors, making it an ideal resource for studying anthocyanin biosynthesis in orchids. In this study, we systematically identified and characterized the structural genes involved in anthocyanin biosynthesis in C. haematodes and compared their roles between C. haematodes and its close relative C. sinense. Pigment analysis revealed that anthocyanins were the predominant pigments in the red-colored tepals of C. haematodes, exhibiting significantly higher levels in dark red (DR) and red (R) accessions compared to lighter color accessions. Transcriptome sequencing identified 20 structural genes, including CHS, F3H, F3’H, DFR, ANS, and UFGT. Phylogenetic analysis indicated close evolutionary relationships with other Cymbidium species. Notably, CsF3’H2 and CsF3’H3 exhibited high expression levels in red tepals, while CsUFGT1–3 and CsDFR1–2 were up-regulated in C. sinense. This suggests species-specific regulatory mechanisms governing pigment production. Subcellular localization assays confirmed cytoplasmic distribution for CsANS, chloroplast localization for CsF3’H2, and cell membrane association for CsF3’H3, implicating diverse functional roles related to anthocyanin transportation and biosynthesis. These findings highlight the functional divergence of structural genes in anthocyanin biosynthesis between C. haematodes and C. sinense, and have specifically identified CsF3’Hs as key genes of red coloration in C. haematodes flowers. This study provides foundational insights into the molecular mechanisms underlying flower color variation among orchids, offering potential targets for future genetic manipulation aimed at enhancing ornamental breeding practices.